MODELING INTERACTIONS OF RAILWAY TRANSPORT AND REGIONAL ROUTE OF INDUSTRIAL SITE - Bashkatov, O. M. (Science and Transport Progress, 2005)
The article is devoted to the issues of interaction between railway transport and fixed route modes of goods delivery to customers, the provision of optimal functional schemes of the route network, in accordance with specific capacities of a transport junction.